Radon Concentration Assessment in Urban Romanian Buildings: A Multistory Analysis - Ștefan Florică; Alexandru-Iulian Lupulescu; Tiberius Dicu; Ancuța Cristina Țenter; Mircea-Claudiu Moldovan; Gabriel-Cristian Dobrei; Luana Copaci; Alexandra Cucoș (Atmosphere)
Radon (Rn 222) is a significant contributor to natural radiation exposure in residential environments such as single-family houses and multistory buildings. This study monitored radon activity concentration (RAC) in 455 apartments in 30 multistory buildings in Buzău, Romania. Integrated measurements of the RAC using CR-39 nuclear track detectors were conducted for a period of 3 to 4 months. The results revealed that the RAC varies between buildings, with an annual average between 33 and 77 Bq/m3. This variation may be attributed to poor ventilation and the chimney effect in common ventilation ducts, which may facilitate radon displacement vertically. Also, apartments with low occupancy or inadequate ventilation showed higher radon levels of up to 285 Bq/m3. The study highlights the potential risk of increased radon exposure in energy-efficient buildings due to poor ventilation, emphasizing the need for special attention to radon mitigation measures in building design. The results emphasize that the RAC is influenced by building characteristics, room use, and ventilation, with significant implications for health risks in urban residential environments.